2020
DOI: 10.3390/biom10040620
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechin (-)-Epigallocatechin-3-Gallate (EGCG) Facilitates Fracture Healing

Abstract: Green tea drinking can ameliorate postmenopausal osteoporosis by increasing the bone mineral density. (-)-Epigallocatechin-3-gallate (EGCG), the abundant and active compound of tea catechin, was proven to be able to reduce bone loss and ameliorate microarchitecture in female ovariectomized rats. EGCG can also enhance the osteogenic differentiation of murine bone marrow mesenchymal stem cells and inhibit the osteoclastogenesis in RAW264.7 cells by modulation of the receptor activator of nuclear factor-kB (RANK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…We found enhanced expression of Ang-1 after treatment with EGCG in LPS-induced ALI. Similar to this, other studies showed beneficial effects on the regenerative capacity of different lung cells [ 48 , 49 ]. The effect of EGCG might be mediated through KLF4, which is a well−known regulator of stem cells and has a role in cell proliferation [ 12 , 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…We found enhanced expression of Ang-1 after treatment with EGCG in LPS-induced ALI. Similar to this, other studies showed beneficial effects on the regenerative capacity of different lung cells [ 48 , 49 ]. The effect of EGCG might be mediated through KLF4, which is a well−known regulator of stem cells and has a role in cell proliferation [ 12 , 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…Lin et al found that percutaneous local injection of EGCG for 2 weeks, 10 µM/L, 40 µL, enhances callus bone volume and increases the tibial mechanical properties. The break load, maximal load, Young’s modulus, and stiffness improved after EGCG treatment with more BMP-2 expression than that found in male rats without EGCG treatment in a tibia fracture model [ 95 ]. Lin et al also demonstrated that local EGCG (10 µM/L, 40 µL) improves femoral defect healing with de novo bone formation by enhancing the bone volume and improving the mechanical properties similar to the above study.…”
Section: Catechinsmentioning
confidence: 99%
“…EGCG (E4143) was purchased from Sigma-Aldrich (St. Louis, MO, USA) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Purity was 99.6% at room temperature.…”
Section: Methodsmentioning
confidence: 99%